A review on courseware for children with down syndrome - Abdul Rahman, Azizah (2014)
Educational courseware is very popular nowadays as an alternative teaching tool for children‟s early education. Courseware that integrates with multimedia elements can bring positive effects by reducing the difficulties in the learning process. Down Syndrome children who face difficulty in learning are being encouraged to utilize educational courseware as a learning tool in their education. Multimedia elements can integrate visual and auditory information into one by primarily presents the visual information first. Thus, other than common coursewares, there are coursewares being designed specifically for Down syndrome children according to their learning behaviours and problems. These coursewares implemented different courseware design techniques with different target subject. This article mainly reviewed on the selected coursewares designed for Down Syndrome children. As Down Syndrome has achieved the highest cases among all the learning disability cases in Malaysia in the recent years, it is crucial to conduct a review on the current research and works in field of courseware learning to understand the current trend and state. Besides, review is conducted on the coursewares in terms of the design techniques and content as a comparison. Thus, improvements and suggestions can be made through the comparison of the coursewares.